CRP levels in autoimmune disease can be specified by measurement of procalcitonin - Schwenger, Vedat; Sis, Jeanne; Breitbart, Andreas; Andrassy, Konrad (Infection, 1998)
Autoimmune diseases (AID) are prone to infection particularly under immunosuppression. The differentiation of infection from active AID is often difficult. In order to specify the diagnostic value of measurement of procalcitonin (PCT) in AID 81 patients with anti-neutrophil cytoplasmic antibody (ANCA)-positive vasculitis were analyzed, 27 with rheumatoid arthritis and 25 patients with systemic lupus erythematosus at various stages of the disease. Although PCT levels (95th percentile) were below 0.5 ng/ml in patients with active systemic lupus erythematosus and rheumatoid arthritis, the cutoff for normal values (95th percentile) in patients with active ANCA-positive vasculitis was 0.89. Therefore PCT levels of <1 ng/ml are recommended as cutoff for invasive infections in patients with ANCA-positive vasculitis. In view of the increased mortality under immunosuppression in patients with AID and additional bacterial infection the measurement of PCT is helpful when an infectious origin is suspected.